2021
DOI: 10.1007/s40888-021-00243-7
|View full text |Cite
|
Sign up to set email alerts
|

Gendering the crisis: austerity and the Covid-19 pandemic in Brazil

Abstract: In this article, by showing that the burden of retrenchment in social spending in Brazil has been overwhelmingly borne by women, we assert that austerity is not gender neutral. Our research investigates the specificities of the gendered impacts of austerity in the country that have rendered Brazilian women structurally more vulnerable to the Covid-19 crisis. We base our argument on a comprehensive literature review summarizing the links between austerity and gender. In the Brazilian case, we explain women’s vu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 39 publications
2
10
0
Order By: Relevance
“…Effectively, several authors have pointed out that those who took over the gap caused by the lack of social protection services during this time were mainly women. This was especially harsh in marginalized communities, namely for those living in urban peripheries and in contexts of poverty and exclusion ( 25 , 44 – 47 ). The increase in the domestic burden harmed women not only in economic terms, but also had direct consequences for their structural position, accentuating pre-existing inequalities and also leading to daily uncertainties that affect their mental wellbeing ( 9 ), as shown in the cases of I., E. and P.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Effectively, several authors have pointed out that those who took over the gap caused by the lack of social protection services during this time were mainly women. This was especially harsh in marginalized communities, namely for those living in urban peripheries and in contexts of poverty and exclusion ( 25 , 44 – 47 ). The increase in the domestic burden harmed women not only in economic terms, but also had direct consequences for their structural position, accentuating pre-existing inequalities and also leading to daily uncertainties that affect their mental wellbeing ( 9 ), as shown in the cases of I., E. and P.…”
Section: Discussionmentioning
confidence: 99%
“…Effectively, the pandemic accelerated the social consequences of dismantling social protection services, adding even more vulnerabilities and fostering processes of exclusion, highlighting the association between the reduction of public spending, the increase in poverty and inequalities as well as general health indicators ( 11 , 25 ). Specifically, there was an increasing concern about the contingencies that this scenario would create to the mental health of the population ( 26 ).…”
Section: Introductionmentioning
confidence: 99%
“…These facts substantiate that gender relations function as a system of dominance shaped by articulations of race, social class, ethnicity, family arrangements, living and work conditions, germane to understanding inequalities in developing countries (Bidegain et al, 2020;Mills, 2003). In accordance with this, long-term racial and gender inequalities in Brazil have been reshaped and enhanced by the pandemic according to social class, regions, and dependence on social support (Bahn et al, 2020, p. 698;Oliveira & Alloatti, 2021). In the country, women are overrepresented among single parents, head of households, and caregivers.…”
Section: Understanding the Crisis From A Feminist Perspectivementioning
confidence: 99%
“…The lack of institutional support intensifies inequality among men and women and differently among women in their diversity. Austerity policies in recent years have compromised severely previous achievements in welfare, food security, gender equality, and poverty eradication (Oliveira & Alloatti, 2021;Rossi et al, 2018). We have shown that gender relations structure the domestic sphere-family/household dimension-in detriment of women, increasing their predominance in part-time, flexible, and informal jobs to accommodate the double burden.…”
Section: Domestic Violence As Part Of the History Of Gender Relations...mentioning
confidence: 99%
See 1 more Smart Citation